PANDANGAN LEMBAGA PENYEDIA MODAL TERHADAP STANDAR KUALITAS LAPORAN SEKTOR PERTANIAN DI KABUPATEN SAMBAS - Denashurya, Nugra Irianta (Fakultas Pertanian, Universitas Janabadra, 2024)
Although the economic growth of Sambas Regency reached 4.63%, the poverty and unemployment rates are still high, reaching 7%, so the government is developing the agricultural sector to overcome this problem with the support of financial institutions that facilitate business capital for prospective entrepreneurs with certain qualifications. The main objective of this study is to identify how financial reports are made by the agricultural sector in Sambas Regency at this time and to understand the views of capital providers on the quality standards of these financial reports. A descriptive approach by collecting data from various sources to describe and interpret current conditions through a questionnaire survey of 30 capital institutions and 10 agricultural sectors in Sambas Regency, which were randomly selected from the population of capital providers and agricultural sectors that met the criteria for financial reports was used in the study. Qualitative methods were used to analyze variables that include the use of financial reports in the agricultural sector and the views of capital providers in Sambas Regency, with a focus on recording by Financial Accounting Standards, understanding financial reports, and report quality based on standards such as Relevance, Understandability, Verifiability, Neutrality, Timeliness, Comparability, and Completeness.